THE PRODUCTION AND DECAY OF TAU-LEPTONS IN E+E- ANNIHILATION AT PETRA ENERGIES - Althoff, M; Braunschweig, W; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Rosskamp, P; Schmitz, D; Siebke, H; Wallraff, W; Eisenmann, J; Fischer, H; Hartmann, H; et al. (Springer-Verlag, 1984)
We have observed τ pair production at average CM energies of 13.9, 22.3, 34.5 and 43.1 GeV. The cross-sections are consistent with QED, the cut off parameters being Λ+>161 GeV and Λ-169 GeV (95% CL). The topological branching fraction of the τ to 1 charged particle, B1, is 0.847±0.011 (stat)-0.013+0.016(syst) and no decays to 5 charged particles were observed resulting in B5<0.007 (95% CL). Within the 3 charged track final state B(τ-→π-π+π- v)/(B(τ-→π- π+π- v)+B(τ-→π-π+π -π0v))=0.37-0.20+0.35 © 1985 Springer-Verlag.